2015
DOI: 10.1111/fcp.12100
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A increases hair follicle growth by suppressing apoptosis‐inducing factor nuclear translocation: a new mechanism

Abstract: Cyclosporine A (CsA) enhances hair growth through caspase-dependent pathways by retarding anagen-to-catagen phase transition in the hair follicle growth cycle. Whether apoptosis-inducing factor (AIF), a protein that induces caspase-independent apoptosis, can regulate the hair follicle cycle in response to CsA is currently unclear. Here, we show that the pro-hair growth properties of CsA are in part due to blockage of AIF nuclear translocation. We first isolate hair follicles from murine dorsal skin. We then us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…ROS inhibits epidermal differentiation through decreasing Notch signaling. Furthermore, inhibiting nuclear translocation of apoptosis-inducing factor (AIF), which was released from mitochondria, retards anagen-to-catagen phase transition of hair follicle growth cycle and leads to decreased hair regeneration ( Lan et al, 2015 ). Further research is needed to reveal if mitochondrial metabolic dysfunction inhibits hair regeneration through regulating HFSCs cell differentiation and its signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…ROS inhibits epidermal differentiation through decreasing Notch signaling. Furthermore, inhibiting nuclear translocation of apoptosis-inducing factor (AIF), which was released from mitochondria, retards anagen-to-catagen phase transition of hair follicle growth cycle and leads to decreased hair regeneration ( Lan et al, 2015 ). Further research is needed to reveal if mitochondrial metabolic dysfunction inhibits hair regeneration through regulating HFSCs cell differentiation and its signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…HF-induced pluripotent stem cells can be induced through gene reprogramming 157 . The HF microenvironment regulates the HF cycle process 163 , 164 . In the future,we will collaborate with other researchers to resolve the problem of hair loss and ensure sustainable clinical applications of effective therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that caspase-dependent apoptosis signalling pathways play an important role in hair cycle transition from the anagen to catagen phase [ 18 , 19 ]. Our recent study showed that cyclosporine A increases hair follicle growth by suppressing AIF nuclear translocation and PARP1 expression, suggesting that the AIF-PARP1-mediated apoptotic pathway, a caspase-independent apoptotic signalling pathway, may be involved in HF transition from anagen to catagen [ 20 ]. However, the roles of AIF-PARP1 and cytochrome c- (Cyto c-) caspase-3 (Cas 3) signalling pathway in hair cycle transition from anagen to catagen and their temporal and spatial regulation are unclear.…”
Section: Introductionmentioning
confidence: 99%